Key Impact of an Uncommon Plasmid on Bacillus amyloliquefaciens subsp. plantarum S499 Developmental Traits and Lipopeptide Production - Molinatto, Giulia; Franzil, Laurent; Steels, Sébastien; Puopolo, Gerardo; Pertot, Ilaria; Ongena, Marc (Frontiers in Microbiology, 2017)
The rhizobacterium Bacillus amyloliquefaciens subsp. plantarum S499 (S499) is particularly efficient in terms of the production of cyclic lipopeptides, which are responsible for the high level of plant disease protection provided by this strain. Sequencing of the S499 genome has highlighted genetic differences and similarities with the closely related rhizobacterium B. amyloliquefaciens subsp. plantarum FZB42 (FZB42). More specifically, a rare 8,008 bp plasmid (pS499) harbouring a rap-phr cassette constitutes a major distinctive element between S499 and FZB42. By curing this plasmid, we demonstrated that its presence is crucial for preserving the typical physiology of S499 cells. Indeed, the growth rate and extracellular proteolytic activity were significantly affected in the cured strain (S499 P-). Furthermore, pS499 made a significant contribution to the regulation of cyclic lipopeptide production. Surfactins and fengycins were produced in higher quantities by S499 P-, whereas lower amounts of iturins were detected. In line with the increase in surfactin release, bacterial motility improved after curing, whereas the ability to form biofilm was reduced in vitro. The antagonistic effect against phytopathogenic fungi was also limited for S499 P-, most probably due to the reduction of iturin production. With the exception of this last aspect, S499 P- behaviour fell between that of S499 and FZB42, suggesting a role for the plasmid in shaping some of the phenotypic differences observed in the two strains.